2021
DOI: 10.1007/s00705-021-04976-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth capability of epidemic influenza viruses in Japan since the 2009 H1N1 pandemic

Abstract: The correlation of viral growth capability (n = 156) with the viral load in nasopharyngeal swabs (n = 76) was assessed. Epidemic influenza A/H1N1, A/H3N2, and B viruses showed a wide range of growth capability (10 4-10 11 copies/mL) in Madin-Darby canine kidney cells. The growth was correlated with the nasopharyngeal viral load (r = 0.53). Six selected strains showed growth-dependent cell death (r = 0.96) in a growth kinetics assay. Epidemic influenza viruses exhibit a wide range of growth capability. Growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Total RNA was extracted using a QIAamp Viral RNA Mini Kit (QIAGEN, Tokyo, Japan). Eight RNA segments of in uenza A virus were simultaneously reverse transcribed and ampli ed using a SuperScript™III One Step RT-Polymerase Chain Reaction (PCR) System (Life Technologies, Tokyo, Japan) with the MBTuni-12/MBTuni-13 primer pair [5,20]. The rst-round PCR products were subjected to a second PCR to amplify NS1 using A-NS-M13 primers (sense: 5-TGTAAAACGACGGCCAGTAGCAAAAGCAGGGTGACAAAGACA-3; antisense: 5-CAGGAAACAGCTATGACCAGTAGAAACAAGGGTGTTTTTTAT-3).…”
Section: Ns1 Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA was extracted using a QIAamp Viral RNA Mini Kit (QIAGEN, Tokyo, Japan). Eight RNA segments of in uenza A virus were simultaneously reverse transcribed and ampli ed using a SuperScript™III One Step RT-Polymerase Chain Reaction (PCR) System (Life Technologies, Tokyo, Japan) with the MBTuni-12/MBTuni-13 primer pair [5,20]. The rst-round PCR products were subjected to a second PCR to amplify NS1 using A-NS-M13 primers (sense: 5-TGTAAAACGACGGCCAGTAGCAAAAGCAGGGTGACAAAGACA-3; antisense: 5-CAGGAAACAGCTATGACCAGTAGAAACAAGGGTGTTTTTTAT-3).…”
Section: Ns1 Sequencingmentioning
confidence: 99%
“…The clinical severity of in uenza virus infection can range from asymptomatic to severe symptomatic illness, and it has been shown that a higher viral load is associated with a more severe case of the disease and a high probability of virus transmission and spread [3,4]. Moreover, one of the probable factors affecting viral load is the intrinsic viral growth capability of the virus [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation